The Effect of Principal Leadership Style and Teacher Work Culture Work on The Performance of Public High School Teachers - Dewi, Nirmala; Ahyani, Nur; Kesumawati, Nila (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2023)
This study aims to see and describe the influence of the principal's leadership style and teacher work culture on the performance of state high school teachers in Lubuk Raja District, OKU Regency. The method used is descriptive quantitative. Data in the form of a questionnaire is classified as quantitative data. The independent variable in this study is the Principal Leadership Style (X1) and Teacher Work Culture (X2), and the dependent variable in this study is Teacher Performance (Y). Data analysis techniques, namely 1) simple and multiple linear correlation test; 2) Significant test using t-test and f-test. The leadership style of the principal and work culture together have a positive effect on teacher performance. The coefficient of the second variable between the second independent variable and the variable in Ry.12 is 0.670. From this coefficient, it can be calculated that the coefficient of determination (R2) is 0.449, meaning that 44.90% of the teacher performance reports can be linked with the principal's leadership style and teacher work culture.